Multi-layered, membrane-integrated microfluidics based on replica molding of a thiol–ene epoxy thermoset for organ-on-a-chip applications. Issue 24 (3rd November 2015) - Sticker, Drago; Rothbauer, Mario; Lechner, Sarah; Hehenberger, Marie-Therese; Ertl, Peter
Abstract : Versatile microfabrication of biocompatible OSTEMER using replica and microinjection molding enables fabrication of complex multi-layered micropump and 3D multi-membrane cell chips. Abstract : In this study we have investigated a photosensitive thermoset (OSTEMER 322-40) as a complementary material to readily fabricate complex multi-layered microdevices for applications in life science. Simple, versatile and robust fabrication of multifunctional microfluidics is becoming increasingly important for the development of customized tissue-, organ- and body-on-a-chip systems capable of mimicking tissue interfaces and biological barriers. In the present work key material properties including optical properties, vapor permeability, hydrophilicity and biocompatibility are evaluated for cell-based assays using fibroblasts, endothelial cells and mesenchymal stem cells. The excellent bonding strength of the OSTEMER thermoset to flexible fluoropolymer (FEP) sheets and poly(dimethylsiloxane) (PDMS) membranes further allows for the fabrication of integrated microfluidic components such as membrane-based microdegassers, microvalves and micropumps. We demonstrate the application of multi-layered, membrane-integrated microdevices that consist of up to seven layers and three membranes that specially confine and separate vascular cells from the epithelial barrier and 3D tissue structures.